THE POSSIBILITIES OF FORMING THE CULTURE OF THE SELF-DEPENDENT WORK OF STUDENTS OF THE COLLEGE: MODELS AND TECHNOLOGIES - S. Konovalov; O. Kozyreva; I. Boykova (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the specifics and possibilities offorming a culture of independent work of College students reflect in modern pedagogical practice qualitative models of solving problems of development, socialization and self-realization of the individual in the hierarchy of detailed contradictions and problems of modern personalized and anthropologically determined choice ("I want, I can, I must, I have"). The theory and practice of modern General, professional and continuing education attaches great importance to General educational methods and models, forms and principles, designs and technologies of activities that guarantee the individual during the period of age-like development and self-realization providing appropriate conditions for the selection and optimization of the quality of solutions to the problems of cooperation and self-affirmation. A clear statement of the problem ofpersonal development of students in the structure of secondary vocational education ensures the success of the formation ofpriorities and the foundations ofproductive formation ofpersonality and multicultural orientation of the individual in the changes taking place in the anthroposphere. The success of solving the problem of forming a culture of independent work of College students can be illustrated at various levels ofproductive formation and choice of the student's personality College.